THE ROLE OF MULTILINGUALISM IN ENHANCING THE LANGUAGE EXPERIENCE OF K-POP FANS - Siti Munawaro; Rini Anjelika; Sawitri Puspita Sari (Al-Irsyad: Journal of Education Science, 2025)
This research explores the role of multilingualism in enriching the language experiences of K-pop fans. The study is driven by the need to understand how multilingual interactions among fans and idols contribute to language acquisition, emotional engagement, and cultural exchange within fandom communities. Employing a descriptive qualitative method, data were gathered through observations, semi-structured interviews, and documentation, focusing on fans from the LUNÉ and ARMY fandoms. This study addresses the gap in previous research, which rarely examines fans' emotional and social experiences with multilingual content. Findings reveal that multilingualism not only motivates fans to learn languages such as Korean, Japanese, and English but also enhances their engagement in transnational fan communities. Fans actively participate in code-switching, use translation tools, and engage in multilingual conversations on platforms like WhatsApp, Weverse, and Twitter. The research concludes that multilingualism significantly shapes fans’ linguistic practices, strengthens emotional bonds with idols, and promotes meaningful cross-cultural communication. These findings underscore the educational and social value of multilingualism within global fandoms, positioning it as a powerful driver of informal language learning.